Challenges of physiotherapy management: type 4 knee arthrofibrosis following traumatic multiple structural injuries of knee in a 16-year old boy: a clinical case report. - Vijayakumar P,; Leonard HJ,; Ayiesah HR, (Department of Surgery, UKM Medical Centre, 2012)
Traumatic knee crush injuries of degloving nature carries a greater risk for the multitude of complications rendering emergency surgical intervention the treatment of choice in the majority of such injuries. These types of injuries commonly result in a unique post- operative complication such as arthrofibrosis and it presents overly challenge for Physiotherapists managing it. In this retrospective single-case report, we describe the challenges of in – and out- patient physiotherapy treatment planning for a 16-year old boy throughout the continuum of care for his knee arthrofibrosis following a series of surgical procedures. As result of his complex medical situation, the time-specific physiotherapy intervention during the immediate post-operative period failed to improve our patient’s knee function. The knee function with regard to range of motion ( especially extension), muscle strength(quadriceps) improved considerably with the adoption of an aggressive physiotherapy intervention approach that included specific quadriceps muscle strengthening, joint mobilization (rotation/traction) in sitting position with legs over the edge of table and contract-relax quadriceps stretching in prone position using theraband.